The Perfect e-Storm: Repurposing Generative Learning Objects - Kofoed, Jens Bruun (HIPHIL Novum, 2014)
Learning objects are often distributed in a static form that is unsuitable for modified reuse, and though certain Learning Management Systems such as LAMS do allow for repurposing, the authoring, adaptation and end user accessibility are all tied to the LAMS platform. The traditional model for reuse, furthermore, has been to focus on content at the expense of pedagogical design. With the generative learning objects (GLOs) authoring tool GLO-Maker, the primary focus of reuse is not the specific learning object itself but rather the pedagogical design that underpins the object. GLOMaker, furthermore, makes these designs accessible to teachers and tutors for adaptation and saves them in packages that can be played from any location into which this package is moved – for example a computer desktop, a web server, a learning management system or an Android mobile phone. Building a repository of repurposable GLOs opens up a wide array of collaboration opportunities for teachers and tutors worldwide, not least in the Majority World. Examples are given on the creation and repurposing of GLO’s on the use of historical method in Biblical exegesis as support for Scandinavian undergraduate and graduate education at the Fjellhaug International University College in Norway and Denmark and their reuse in a Majority World context.